The Changing Phenotype of Inflammatory Bowel Disease - Carthage Moran; Donal Sheehan; Fergus Shanahan (Gastroenterology Research and Practice)
It is widely known that there have been improvements in patient care and an increased incidence of Inflammatory Bowel Disease (IBD) worldwide in recent decades. However, less well known are the phenotypic changes that have occurred; these are discussed in this review. Namely, we discuss the emergence of obesity in patients with IBD, elderly onset disease, mortality rates, colorectal cancer risk, the burden of medications and comorbidities, and the improvement in surgical treatment with a decrease in surgical rates in recent decades.